Anti-depression effect and mechanism of Suanzaoren Decoction on mice with depression. Issue 2 (March 2021) - Zhang, Huan; Ren, Yumei; Lv, Meiqi; Xie, Mengting; Wang, Kai; Yang, Mengjie; Lv, Chengqi; Li, Xiaobing
Abstract: Objective: To study the therapeutic effect and mechanism of Suanzaoren Decoction on mice with depression. Methods: A model of depression was prepared by chronic unpredictable stimulation and reserpine induction. Behavioral tests, determination of norepinephrine and dopamine were performed. Results: The behavioral indicators of the model group were reduced, and the expression of norepinephrine and dopamine was decreased. Conclusion: Suanzaoren Decoction has an effect on the increase of serum norepinephrine and dopamine content, indicating that the jujube seed Soup has a certain effect on depression.